How fast and how dialogic should review processes of an Open Access music therapy journal be?. (1st June 2016) - Rolvsjord, Rune; Hadley, Susan; McFerran, Katrina; Stige, Brynjulf
Abstract : Background : As an Open Access journal, Voices: A World Forum for Music Therapy has a profile and vision that highlights cultural and critical awareness as well as dialogic review processes. But how do authors perceive the relationship between the journal's vision and its practice of reviewing articles? Objective : To examine how authors perceive review processes and how article reviewers and journal editors could contribute to expedient reviews. Methods : An author survey combined with collective, critical reflections among editors on review policies and practices. Discussion : Review processes need to be tailored to authors' experience, intentions, and cultural/disciplinary background, as well as to the journal's vision. These considerations imply that there are conflicts of interest in review processes that require negotiations. Conclusion : The feedback provided about what editors and reviewers could do differently can be categorised into three main areas. The largest category is of authors who are entirely happy with their experience of the journal, while there are also groups of authors who want faster reviewing and more dialogues in review processes.